2012
DOI: 10.1021/es204572g
|View full text |Cite
|
Sign up to set email alerts
|

Higher Mass-Independent Isotope Fractionation of Methylmercury in the Pelagic Food Web of Lake Baikal (Russia)

Abstract: Mercury undergoes several transformations that influence its stable isotope composition during a number of environmental and biological processes. Measurements of Hg isotopic mass-dependent (MDF) and mass-independent fractionation (MIF) in food webs may therefore help to identify major sources and processes leading to significant bioaccumulation of methylmercury (MeHg). In this work, δ(13)C, δ(15)N, concentration of Hg species (MeHg, inorganic Hg), and stable isotopic composition of Hg were determined at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
117
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(142 citation statements)
references
References 58 publications
24
117
1
Order By: Relevance
“…Regarding Hg isotopic composition, it was determined by cold-vapor MC-ICP-MS (Nu Plasma, Nu Instruments) as detailed elsewhere (Perrot et al, 2012). Analytical uncertainty was determined as the largest 2SD corresponding to the sample or to the measurement of the UM-Almadén secondary standard during each session.…”
Section: Hg Speciation and Stable Isotopic Analysesmentioning
confidence: 99%
“…Regarding Hg isotopic composition, it was determined by cold-vapor MC-ICP-MS (Nu Plasma, Nu Instruments) as detailed elsewhere (Perrot et al, 2012). Analytical uncertainty was determined as the largest 2SD corresponding to the sample or to the measurement of the UM-Almadén secondary standard during each session.…”
Section: Hg Speciation and Stable Isotopic Analysesmentioning
confidence: 99%
“…By combining MDF and MIF, previous studies have identified sources and gained insight into complex biogeochemical processes governing MMHg in many natural ecosystems (Gantner et al, 2009;Senn et al, 2010;Gehrke et al, 2011;Point et al, 2011;Day et al, 2012;Perrot et al, 2012;Tsui et al, 2012Tsui et al, , 2013Tsui et al, , 2014Blum et al, 2013;Demers et al, 2007;Kwon et al, 2014Kwon et al, , 2015.…”
mentioning
confidence: 99%
“…Particularly in aquatic ecosystems, the analysis of Hg isotope ratios in fish tissues has become a useful tool for monitoring complex biological processes such as bioaccumulation and trophic transfer, and consequently for inferring bioaccumulative sources of MMHg (Gantner et al, 2009;Senn et al, 2010;Gehrke et al, 2011;Point et al, 2011;Perrot et al, 2012;Tsui et al, 2012Tsui et al, , 2013Tsui et al, , 2014Blum et al, 2013;Kwon et al, 2014Kwon et al, , 2015. For instance, fish feeding experiments documented the absence of d 202 Hg and D 199 Hg fractionation during bioaccumulation and trophic transfer of both IHg and MMHg to juvenile freshwater (i.e., yellow perch) and marine fish (i.e., amberjack) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Species-specific Hg isotope fractionation of MeHg has recently been observed in biological samples [138,139] and in chemical transformation processes such as methylation [140] and demethylation [138,141,142]. The fingerprint of mass-dependent and -independent fractionation of MeHg in natural environmental samples was suggested to be a good indicator of important processes in the global cycle of MeHg and will be helpful to understand and quantify these processes [138].…”
Section: Chromatographic Separation Coupled With Mc-icp-ms To Measurementioning
confidence: 99%